The Relative Importance of Education and Criminal Justice Costs and Benefits in Economic Evaluations: A Best–Worst Scaling Experiment - Pokhilenko, Irina (Pharmacoeconomics, 2020)
OBJECTIVES: Mental and behavioural disorders (MBDs) and interventions targeting MBDs lead to costs and cost savings in the healthcare sector, but also in other sectors. The latter are referred to as intersectoral costs and benefits (ICBs). Interventions targeting MBDs often lead to ICBs in the education and criminal justice sectors, yet these are rarely included in economic evaluations. This study aimed to investigate the attitudes held by health economists and health technology assessment experts towards education and criminal justice ICBs in economic evaluations and to quantify the relative importance of these ICBs in the context of MBDs. METHODS: An online survey containing open-ended questions and two best–worst scaling object case studies was conducted in order to prioritise a list of 20 education ICBs and 20 criminal justice ICBs. Mean relative importance scores for each ICB were generated using hierarchical Bayes analysis. RESULTS: Thirty-nine experts completed the survey. The majority of the respondents (68%) reported that ICBs were relevant, but only a few (32%) included them in economic evaluations. The most important education ICBs were “special education school attendance”, “absenteeism from school”, and “reduced school attainment”. The most important criminal justice ICBs were “decreased chance of committing a crime as a consequence/effect of mental health programmes/interventions”, “jail and prison expenditures”, and “long-term pain and suffering of victims/victimisation”. CONCLUSIONS: This study identified the most important education and criminal justice ICBs for economic evaluations of interventions targeting MBDs and suggests that it could be relevant to include these ICBs in economic evaluations. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40273-020-00966-8) contains supplementary material, which is available to authorized users.